The use of auto-antibody testing in the evaluation of interstitial lung disease (ILD) – A practical approach for the pulmonologist. (April 2016) - Bahmer, Thomas; Romagnoli, Micaela; Girelli, Francesco; Claussen, Martin; Rabe, Klaus F.
Abstract: Interstitial lung diseases (ILD), also defined as diffuse parenchymal lung diseases (DPLD) include a heterogeneous group of pulmonary disorders. They may be caused by an underlying connective tissue disease (CTD), Rheumatoid Arthritis (RA) or ANCA-associated Vasculitis (AAV). Pulmonary manifestations of these conditions may also precede systemic onset and therefore, pulmonologists may be confronted with diagnosing a systemic rheumatic disease. For the discrimination of CTD-related ILD and idiopathic interstitial pneumonia (IIP), serological testing is recommended. After careful reviewing the available literature, we suggest a serologic diagnostic algorithm for pulmonologists dealing with ILD-patients. This algorithm depicts the consensus for antibody testing that was reached amongst authors. Obviously this consensus approach requires further validation in everyday practice and leaves room for local adaption of the diagnostic strategy depending on the availability of diagnostic capacity and cost. It is our hope, however, that the rational and stepwise approach of serological testing for ILD will ultimately save unnecessary expenses associated with general laboratory screening. Finally a broader consensus on the strategy for laboratory testing in ILD in general might also improve the detection level of these relatively rare diseases and this will ultimately improve management and care of patients suffering from these complex disorders. Highlights: Interdisciplinary and clinically oriented approach to patients with unclear ILD. Pragmatic assistance in the serologic delineation of CTD-ILD and IIP. Description of the predictive value of single auto-antibody tests in the context of ILD. Special focus on ANA fluorescence pattern. Suggestion of a stepwise serologic algorithm, based on available evidence, clinical expertise and cost.